Molecular Characterization of Somatic Alterations in Dukes’ B and C Colorectal Cancers by Targeted Sequencing - Abdul, Shafina-Nadiawati; Ab Mutalib, Nurul-Syakima; Sean, Khor S.; Syafruddin, Saiful E.; Ishak, Muhiddin; Sagap, Ismail; Mazlan, Luqman; Rose, Isa M.; Abu, Nadiah; Mokhtar, Norfilza M.; Jamal, Rahman (Frontiers in Pharmacology, 2017)
Despite global progress in research, improved screening and refined treatment strategies, colorectal cancer (CRC) remains as the third most common malignancy. As each type of cancer is different and exhibits unique alteration patterns, identifying and characterizing gene alterations in CRC that may serve as biomarkers might help to improve diagnosis, prognosis and predict potential response to therapy. With the emergence of next generation sequencing technologies (NGS), it is now possible to extensively and rapidly identify the gene profile of individual tumours. In this study, we aimed to identify actionable somatic alterations in Dukes’ B and C in CRC via NGS. Targeted sequencing of 409 cancer-related genes using the Ion Ampliseq™ Comprehensive Cancer Panel was performed on genomic DNA obtained from paired fresh frozen tissues, cancer and normal, of Dukes’ B (n = 10) and Dukes’ C (n = 9) CRC. The sequencing results were analysed using Torrent Suite, annotated using ANNOVAR and validated using Sanger sequencing. A total of 141 somatic non-synonymous sequence variations were identified in 86 genes. Among these, 64 variants (45%) were predicted to be deleterious, 38 variants (27%) possibly deleterious while the other 39 variants (28%) have low or neutral protein impact. Seventeen genes have alterations with frequencies of ≥ 10% in the patient cohort and with 14 overlapped genes in both Dukes’ B and C. The adenomatous polyposis coli gene (APC) was the most frequently altered gene in both groups (n = 6 in Dukes’ B and C). In addition, TP53 was more frequently altered in Dukes’ C (n = 7) compared to Dukes’ B (n = 4). Ten variants in APC, namely p.R283*, p.N778fs, p.R805*, p.Y935fs, p.E941fs, p.E1057*, p.I1401fs, p.Q1378*, p.E1379* and p.A1485fs were predicted to be driver variants. APC remains as the most frequently altered gene in the intermediate stages of CRC. Wnt signalling pathway is the major affected pathway followed by P53, RAS, TGF-β and PI3K signaling. We reported the alteration profiles in each of the patient which has the potential to affect the clinical decision. We believe that this study will add further to the understanding of CRC molecular landscape.